Association between living near to a non-sanitary landfill, fingernail cadmium level and health symptoms among children in Nilai - Syed Ismail, Sharifah Norkhadijah; Y., Nurizzati; Praveena, Sarva Mangala; Zainal Abidin, Emilia; E. J., Dora (Community Health Society Malaysia, 2015)
Background: Living in proximity to landfill could expose children to heavy metals such as Cadmium that can reduce immune system function and lead to an increased risk of infections. Study was aimed to determine the accumulation of Cd in fingernails and the associated health symptoms among school children living in a proximity to non-sanitary landfill sites.